2017
DOI: 10.3126/ajms.v8i5.17633
|View full text |Cite
|
Sign up to set email alerts
|

Study of febrile thrombocytopenia in Malwa region of India

Abstract: Background: Febrile thrombocytopenia is the thrombocytopenia associated with fever. Diseases which commonly present with fever and thrombocytopenia are malaria, leptospirosis, septicemia, typhoid, arbovirus diseases such as dengue.Aims and Objectives: The study was intended to know the underlying etiology of febrile thrombocytopenia in Malwa region and its various presentations.Materials and Methods: This study was conducted at Department of General Medicine of a tertiary care centre for two years. Five-hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…HIV was reported as viral fever in the study by Modi T et al 6 , 5% patients of study by Gondhali MP et al 12 and which was reported as 1(0.11%) patient in our study. In our study 59.53% patients had platelet count within 50000-100000/ mm 3 range compared to 57.14% in study by Gandhi A A et al 5 , 53% in Fawas M N et al 7 , 53.8% in Yadav and Singhai et al 11 In our study 4% of patients had platelet count less than 20000, compared to study by Gandhi A A et al 5 which is 13.39%, in Fawas M N et al 7 5% and in Yadav and Singhai et al 11 11.8%. Bleeding manifestations were seen in 24.3% patients in our study as compared to study by Yadav and Singhai et al 11 which is 7.8%, in Fawas M N et al 7 17%, in Gondhali MP et al 12 24%.Petechiae was the commonest bleeding manifestation of 14% in our study followed by mucosal bleeding in 10.3%patients which is similar to study by Gondhali MP et al 12 In our study when the platelet count was between 20000-50000 / mm 3 .…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…HIV was reported as viral fever in the study by Modi T et al 6 , 5% patients of study by Gondhali MP et al 12 and which was reported as 1(0.11%) patient in our study. In our study 59.53% patients had platelet count within 50000-100000/ mm 3 range compared to 57.14% in study by Gandhi A A et al 5 , 53% in Fawas M N et al 7 , 53.8% in Yadav and Singhai et al 11 In our study 4% of patients had platelet count less than 20000, compared to study by Gandhi A A et al 5 which is 13.39%, in Fawas M N et al 7 5% and in Yadav and Singhai et al 11 11.8%. Bleeding manifestations were seen in 24.3% patients in our study as compared to study by Yadav and Singhai et al 11 which is 7.8%, in Fawas M N et al 7 17%, in Gondhali MP et al 12 24%.Petechiae was the commonest bleeding manifestation of 14% in our study followed by mucosal bleeding in 10.3%patients which is similar to study by Gondhali MP et al 12 In our study when the platelet count was between 20000-50000 / mm 3 .…”
Section: Discussioncontrasting
confidence: 43%
“…7 Rickettsial fever was the second common cause of febrile thrombocytopenia with increasing trend from 21.9% in 2016 to 26% in 2017 and 33.4% in 2018.Rickettsial fever was suspected in 6.6% patients of study by Suneetha et al 8 conducted in Mysuru, and also reported in 2.5% patients in study by Hariprasad S et al 9 conducted in raichur, Karnataka. Undifferentiated fever was the third common cause of febrile thrombocytopenia and was 29.3% in 2016, 9% in 2017 and 12.2% in 2018.Undifferentiated fever was reported as most commonest cause in studies by Suneetha et al (61.4%) 8 , Naveen Kulkarni et al(62.5%) 10 , Yadav and Singhai et al(35.6%) 11 , The other causes of febrile thrombocytopenia in our study was septicemia in 1.9%, enteric fever in 1.6%, malaria in 0.9%, malignancy in 0.23% with 2 cases of acute leukemia, HIV in 0.11%. The incidence of septicemia was 0.8% in the study by Fawas M N et al 7 , 8% each in the studies by suneetha et al 8 , Naveen Kulkarni et al 10 , 12.5% in the study by Hariprasad S et al 9 The incidence of enteric fever was 6.5% in the study by Naveen Kulkarni et al 10 , 2% in the study by suneetha et al 8 , 1.8% in the study by Yadav and Singhai et al 11 , 0% in the studies by Fawas M N et al 7 and Hariprasad S et al 9 The incidence of malaria is 28.5% in the study by Hariprasad S et al 9 , 24.4% in the study by Yadav and Singhai et al 11 , 13% in the study by Naveen Kulkarni et al 10 and lower incidence of 2% in the study by Suneetha et al 8 The incidence of hematological malignancy was reported of 0.6% in the study by Yadav and Singhai et al 11 , 1.79% in the study by Gandhi A A et al 5 which was 0.23% in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Yadav V et al's study [24] on a sample of 500 cases included 298 males and 202 females. Viral fever was the most frequent cause of febrile thrombocytopenia in our study (35.6%).…”
Section: Discussionmentioning
confidence: 99%